AFM-based bivariate morphological discrimination of apoptosis induced by photodynamic therapy using photosensitizer-functionalized gold nanoparticles. Issue 101 (30th September 2015) - Al-Majmaie, Rasoul; Kennedy, Eamonn; Al-Rubeai, Mohamed; Rice, James H.; Zerulla, Dominic
Abstract : Typical examples of the morphology of one viable and one apoptotic cell together with the statistical analysis of a larger cell ensemble subsequent to photodynamic treatment. Abstract : The apoptosis of cancer cells is linked to characteristic changes in cell properties which include many morphological parameters. Recent studies have indicated that using atomic force microscopy (AFM) to identify mechanical properties of cells at a subcellular scale is an extremely precise way of evaluating the influence of therapies on single cells and subcellular features. This study outlines how apoptosis initiated by photodynamic therapy using photosensitizer conjugated gold nanoparticles mediates the morphological properties of single colon cancer cells, and how these properties can in turn be used as an efficient classifier of cell health. We describe a bivariate statistical classifier of two independent AFM measurements of cell properties (total volume and membrane roughness) which exhibits apoptotic detection accuracy comparable to the prevailing biological standards.